2021
DOI: 10.1101/2021.07.07.21260092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Covid-19 Syndrome, Inflammatory Markers and Sex Differences

Abstract: INTRODUCTION AND OBJECTIVEPost-COVID syndrome (PCS) is a poorly-known entity. Underlying low-grade inflammation (LGI) has been theorized as one of its pathophysiological mechanisms. We aimed to investigate a possible relationship between PCS and an increase in inflammation markers, in a sex-stratified analysis.PARTICIPANTS AND METHODSMild cases of COVID-19 according to the WHO classification followed-up in a Primary Care Center, were included. We collected epidemiological data (age, sex, body mass index -BMI-,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recently, multiple studies have reported a growing number of COVID-19-infected children developing this systemic in ammatory illness-now formally recognized as MIS-C (31)(32)(33)(34). It is theorized that MIS-C may manifest as part of a post-infectious immune response -similar to the mechanism involved in the COVID-19-related autoimmune meningoencephalitis observed in adults (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have reported a growing number of COVID-19-infected children developing this systemic in ammatory illness-now formally recognized as MIS-C (31)(32)(33)(34). It is theorized that MIS-C may manifest as part of a post-infectious immune response -similar to the mechanism involved in the COVID-19-related autoimmune meningoencephalitis observed in adults (35).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 studies reported a significant association with fatigue. More women were fatigued, 42 52 63–66 68 96 98 99 123 125 128 130 133 136 139–152 they (54.3%) reported more severe/moderate fatigue than men (29.6%)86 129 and had significantly lower vitality scores (M=81.80) compared with men (M=83.25) 124. However, 16 used an unvalidated instrument potentially affecting results.…”
Section: Resultsmentioning
confidence: 99%
“…Several articles analyzed the association of inflammatory and complete blood count (CBC) markers with complications of long COVID-19. 3 , 4 , 10 , 14 – 24 Hs-CRP and ferritin were correlated with complications of long COVID-19 in patients infected with the Alpha variant. However, the Delta variant revealed a more significant correlation with Hs-CRP, red cell distribution width (RDW), and NLR.…”
Section: Introductionmentioning
confidence: 94%